2008
DOI: 10.1007/s11596-008-0331-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lutein on the growth and migration of bovine lens epithelial cells in vitro

Abstract: The effects of lutein on the growth and migration of bovine lens epithelial cells (BLECs) in vitro were observed in an attempt to find a drug that can prevent after-cataract. BLECs were cultured in vitro and different concentrations of lutein were added to the BLECs cultures of the second and third generations. The effects of lutein on the proliferation of BLECs in vitro were examined by the MTT method, and the migration of BLECs was evaluated by a scratch wound assay. The results showed that: (1) Lutein at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There are conflicting reports on the impact of the concentration of free lutein on cell viability [ 23 , 39 ]. Incubation of HLE cells with 0.1 to 10 μM of lutein was found to have no impact on cell viability [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting reports on the impact of the concentration of free lutein on cell viability [ 23 , 39 ]. Incubation of HLE cells with 0.1 to 10 μM of lutein was found to have no impact on cell viability [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of HLE cells with 0.1 to 10 μM of lutein was found to have no impact on cell viability [ 23 ]. In a separate report, a concentration effect of lutein on the proliferation and migration of bovine lens epithelial cells was identified [ 39 ]. Although differences in tested concentrations and lutein sources make it difficult to draw comparisons between these reports, lutein concentration in our study is correlated with the viability of HLE cells and is a factor which should be considered in future in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…It improves age-related macular disease and can be a safe treatment for cataracts. Y. Hu and colleagues showed in vitro experiments that lutein has the ability to prevent cataracts in bovine lens epithelial cells by inhibiting lens cell proliferation and migration at a concentration of higher or equal 1 micromol / L [231]. Y. Li and coworkers revealed their study on the human breast cancer cell lines MDA-MB-157 and MCF-7 that lutein inhibits cell proliferation in dose-dependent manner.…”
Section: Carotenoids and Clinical Applicationsmentioning
confidence: 99%
“…Cataract, as well as AMD, is a growing health problem responsible for vision loss [ 110 ], due to oxidation of lens structures. Antioxidants, specifically L, might be a safe treatment for this condition, and in-vitro studies have demonstrated that L is able to prevent cataract in bovine cells by inhibiting the proliferation and migration of lens cells [ 111 ], as well as to prevent ultraviolet damage in human lens cells [ 109 ]. A few observational studies have found a significant correlation between high L plasma concentrations and a low risk for developing cataract [ 112 , 113 , 114 , 115 ], and a negative association has also been reported between daily L intake and the risk of cataract, especially nuclear cataract [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Lutein and Eye Disturbancesmentioning
confidence: 99%